2018
DOI: 10.1080/00665983.2018.1504859
|View full text |Cite
|
Sign up to set email alerts
|

Histories of deposition: creating chronologies for the Late Bronze Age–Early Iron Age transition in Southern Britain

Abstract: The Late Bronze Age-Early Iron Age midden sites of Southern Britain are amongst the richest archaeological sites in the country. The organic accumulations contain substantial quantities of animal bone, decorated ceramics, metalwork and other objects; the often deep stratigraphy allows for a number of changes in material culture and depositional practices, food production and consumption, and shifts in social identities, to be traced through time. The well-stratified assemblages also provide useful materials fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…However, as illustrated in a range of recent work, and this Therasia case study again highlights, various method strategies using informative priors, as relevant or bespoke to the particular samples and context(s) involved, are now available that much better enable chronological resolution via Bayesian Chronological Modeling for contexts that lie at the time of plateaus in the radiocarbon calibration curve (e.g. Manning et al 2018a;2018c;2019;2020a;Waddington et al 2019;Meadows et al 2020;Birch et al 2021;Rose et al 2022;Manning and Birch 2022). With increasing radiocarbon measurement accuracy and precision as standard via rigorous sample pretreatment and modern AMS 14 C analysis, and a better (ideally annually informed) radiocarbon calibration curve adding resolution (as already in the period 1700-1500 BC discussed in this paper), the application of such methods promises increasingly to allow high-resolution dating on plateaus almost as effectively as on slopes in the radiocarbon calibration curve.…”
Section: Dating On Plateaus In the Radiocarbon Calibration Curvementioning
confidence: 99%
See 1 more Smart Citation
“…However, as illustrated in a range of recent work, and this Therasia case study again highlights, various method strategies using informative priors, as relevant or bespoke to the particular samples and context(s) involved, are now available that much better enable chronological resolution via Bayesian Chronological Modeling for contexts that lie at the time of plateaus in the radiocarbon calibration curve (e.g. Manning et al 2018a;2018c;2019;2020a;Waddington et al 2019;Meadows et al 2020;Birch et al 2021;Rose et al 2022;Manning and Birch 2022). With increasing radiocarbon measurement accuracy and precision as standard via rigorous sample pretreatment and modern AMS 14 C analysis, and a better (ideally annually informed) radiocarbon calibration curve adding resolution (as already in the period 1700-1500 BC discussed in this paper), the application of such methods promises increasingly to allow high-resolution dating on plateaus almost as effectively as on slopes in the radiocarbon calibration curve.…”
Section: Dating On Plateaus In the Radiocarbon Calibration Curvementioning
confidence: 99%
“…tree-ring series) or typological information, and/or (ii) prior knowledge of total sequence length and/or of any intra-sequence associations (e.g. Waddington et al 2019; Meadows et al 2020; Manning et al 2020a; Manning and Birch 2022; Rose et al 2022). In the absence of such forms of additional constraints, sequences of dates on a plateau will end up defining too wide a calendar age range and will likely end up suggesting dating probability that is either too old or too recent.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using Bayesian chronological modelling have demonstrated that is possible to model case studies on 14 C calibration plateaus, although applications tend to target materials whose dates are constrained by strong prior information based e.g. on stratigraphy [52,53], floating tree-ring series [54,55], or archaeogenetic evidence [56]. This study however employs relatively weak constraints, assuming that artefacts sharing certain characteristics (i.e.…”
Section: Modelling Change Within a Bayesian Frameworkmentioning
confidence: 99%
“…At East Chisenbury, Wiltshire, recent excavations of the enclosure ditch surrounding the well-known midden, as well as post-holes and other features immediately adjacent to it, produced several fragments of human bone (Andrews 2021; for discussion of the overall date range of the midden itself, see Waddington et al 2019). The disarticulated ulna of a child aged 8-12 was deposited in the enclosure ditch (middle fill 128).…”
Section: Depositional Process and The Treatment Of The Dead In The Mi...mentioning
confidence: 99%